The paradoxes of importing foreign sports players into Singapore's sporting arena. - Lee, Celeste. (2013)
Sports play a very major role in our lives and it is prevalent that we acknowledge sportsmen and their successes in our society. Sports events are ubiquitous and it is the norm that we see sporting events on the television and on social media. Even more so, there is an influx of foreign players in the Singapore's sporting arena and this has come to my interest to study with regards to this phenomenon. However much we understand and know the reasons of importing foreign players to represent Singapore in major sporting events, many still wonder why is there a need to bring in so many foreign players to play for our country. Controversies which relates with the imported foreign players also come into the picture. Analytical discussions will be made to give a bigger and clearer picture of this highlighted phenomenon of these imported foreign players into Singapore's sporting arena.